Inovasi Pengusir Hama Tenaga Surya untuk Optimalisasi Hasil Pertanian di Desa Bulupitu Kecamatan Gondanglegi Kabupaten Malang - Nurmalasari, Riana; Tuwoso, Tuwoso; Sutadji, Eddy; Sunaryo, Nonny Aji; P.P.S, Gladis Viona (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
One of the things that prevents harvest outcomes from being as good as expected is the pests. Making a pest repellent with solar power is one attempt to tackle pests. The purpose of this tool is to lessen crop losses brought on by pests such as birds, insects, and rats. This device uses eco-friendly frequency sounds to ward off pests without jeopardizing the ecosystem's ability to sustain itself. This study sought to determine how using pest repellents could improve agricultural output while maintaining the sustainability of the surrounding ecosystem. Based on data analysis findings, it was determined that pest repellents and agricultural productivity had a significant positive relationship for the sustainability of the environmental ecosystem (R 0.662 and sig.0,000).